The knight at dawn - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2013)
Eight-year-old Jack and his younger sister Annie use the magic tree house to travel back to the Middle Ages, where they explore a castle and are helped by a mysterious knight.
"A first Stepping Stone book."
Five Owls.
3.3
3-6
Keywords: Annie (Fictitious character : Osborne) -- Juvenile fiction; Castles -- Juvenile fiction; Jack (Fictitious character : Osborne) -- Juvenile fiction; Knights and knighthood -- Juvenile fiction; Magic -- Juvenile fiction; Middle Ages -- Juvenile fiction; Time travel -- Juvenile fiction; Tree houses -- Juvenile fiction; Annie (Fictitious character : Osborne) -- Fiction; Castles -- Fiction; Jack (Fictitious character : Osborne) -- Fiction; Knights and knighthood -- Fiction; Magic -- Fiction; Middle Ages -- Fiction; Time travel -- Fiction; Tree houses -- Fiction; Annie (Fictional character : Osborne) -- Fiction; Castles -- Fiction; Jack (Fictional character : Osborne) -- Fiction; Knights and knighthood -- Fiction; Magic -- Fiction; Middle Ages -- Fiction; Time travel -- Fiction; Tree houses -- Fiction